Knowledge, Attitudes, and Practices Regarding Antibiotic Usage Among the General Population of Dhaka City (Bangladesh Journal of Infectious Diseases, 2025)
Background: Antibiotic resistance is a growing global health threat, causing treatment failures and increased healthcare costs.Objective: This study was aimed to investigate the knowledge, attitudes, and practices (KAP) surrounding antibiotic use among the general population of Dhaka city.Methodology: The cross-sectional descriptive study was conducted at the epidemiology department of the State University of Bangladesh, Dhaka, Bangladesh from July to December 2013 for a period of 6 months. They are above 18 years old; they are aware of the term "antibiotics". Participants were excluded if he/she refused to participate in the study and the participants who were unable to provide information due to physical or mental illness. Three selected wards in Dhaka city were included in this study, with a total sample size of 120. A self-administered pre-tested questionnaire prepared in English was used for data collection. Data were presented as mean ± SD, with prevalence rates as percentages. Tests of significance and cross-tabulation were used to determine the relation between socio-demographic characteristics and antibiotic use.Results: The study revealed that among the respondents, 68(56.7%) used antibiotics without a doctor’s prescription (self-medication). In this study, a total of 112(93.33%) respondents used antibiotics, while only 8(6.67%) did not use antibiotics. 32(47.1%) respondents selected antibiotics from a previous doctor’s prescription, and 30(44.1%) based their choice on the community pharmacist’s recommendation. Among the respondents, 85(71.4%) used antibiotics due to fever, 47(39.5%) due to cough, 39(32.8%) due to diarrhea, and 37(31.1%) due to aches and pains. Out of the 120 respondents, the majority, about 72(60%), had poor knowledge, followed by 40(33.3%) who had satisfactory knowledge, and only 8(6.7%) who had good knowledge. A statistically significant association was found between self-medication and the level of knowledge (P-value